Object-oriented technology [electronic resource]: ECOOP 2006 workshop reader ; ECOOP 2006 workshops, Nantes, France, July 3-7, 2006 : final reports - ECOOP 2006 (2006 : Nantes, France); Sudholt, Mario; Consel, C. (Charles); SpringerLink (Online service) (Berlin, Heidelberg : Springer-Verlag Berlin Heidelberg, 2007)
57